Impact of annual bone loss and different bone quality on dental implant success – A finite element study. (1st December 2017) - Linetskiy, Igor; Demenko, Vladyslav; Linetska, Larysa; Yefremov, Oleg
Abstract: Background: For dental implant success, experimentally established thresholds should limit bone stresses and strains. From these metrics, the ultimate functional load, which determines the implant load-carrying capacity, can be calculated. Obviously, its decrease due to bone loss shortens implant service life. A comparison of how bone loss affects the ultimate functional loads of various implants can provide the clinician with meaningful feedback concerning the suitability and longevity of implants. The aim of this study is to evaluate the lifetime of different dental implants placed in I–IV bone types on the basis of a comparison of their ultimate functional loads with consideration of the bone loss factor. Method: Von Mises stress and first principal strain distributions in bone-implant interface were studied and ultimate functional loads were calculated. Models of I–IV bone types were designed. 3.3 × 8.0 mm (A), 4.1 × 12.0 mm (B) and 4.8 × 14.0 mm (C) implants were analyzed at 10 levels of bone loss. Ultimate functional loads, which generated the ultimate von Mises stress and first principal strain in bone, were computed. Results: For the implants A, B, and C placed in type I bone, ultimate functional load values were above 120.92 N experimental functional load, which corresponded to 10+, 10+, and 10 + years of service with 0.2 mm annual bone loss. For type II bone, the lifetime was 4, 10+, and 10 + years. For type III bone, the lifetime was 4, 5, and 5 years. For type IV bone, first principal strains were initially deleterious for all implants. Conclusions: In oral implantology, bone loss is an essential factor for implant longevity prognosis. While evaluating implant load-carrying capacity, clinicians should take into account the factor of implant longevity decrease. Highlights: Bone loss is both cause and effect of bone overload. In bone loss, bone quality and implant size have major impact on stresses and strains. Implant longevity is achieved by stress and strain limitation for types I-III bone. For this specific scenario, type IV bone is improper for implant placement in view of bone loss.